2018
DOI: 10.1101/272039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific enrichment of hyperthermophilic electroactive Archaea from deep-sea hydrothermal vent on electrically conductive support

Abstract: 11While more and more investigations are done to isolate hyperthermophilic exoelectrogenic 12 communities from environments, none have been performed yet on deep-sea hydrothermal vent. 13

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…Moreover, Archaeoglobus fulgidus has been recently shown to grow on iron by directly snatching electrons under carbon starvation during corrosion process (Jia et al, 2018). Furthermore, Ferroglobus and Geoglobus species were shown to be exoelectrogens in pure culture in a microbial electrosynthesis cell (Yilmazel et al, 2018) and were enriched during a study within a microbial electrolysis cell (Pillot et al, 2018(Pillot et al, , 2019. Interestingly, some studies have shown that Geobacter species are capable of bidirectional electron transfer using the same mechanism (Pous et al, 2016).…”
Section: Archaeoglobales As Systematic (Electro)lithoautotrophs Of Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Archaeoglobus fulgidus has been recently shown to grow on iron by directly snatching electrons under carbon starvation during corrosion process (Jia et al, 2018). Furthermore, Ferroglobus and Geoglobus species were shown to be exoelectrogens in pure culture in a microbial electrosynthesis cell (Yilmazel et al, 2018) and were enriched during a study within a microbial electrolysis cell (Pillot et al, 2018(Pillot et al, , 2019. Interestingly, some studies have shown that Geobacter species are capable of bidirectional electron transfer using the same mechanism (Pous et al, 2016).…”
Section: Archaeoglobales As Systematic (Electro)lithoautotrophs Of Thmentioning
confidence: 99%
“…Archaeoglobales strongly correlated to Thermococcales (Pillot et al, 2018(Pillot et al, , 2019. Moreover, members of these two groups have frequently been found together in various hydrothermal sites on the surface of the Earth (Corre et al, 2001;Nercessian et al, 2003;Takai et al, 2004;Jaeschke et al, 2012), where they are considered as potential primary colonizers of their environments (33)(34)(35)(36).…”
Section: Enrichment Of Rich Heterotrophic Biodiversity From Electrotrmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have reported on the diversity of EAMs from extreme environments. These include, for instance, highly saline [17][18][19] , extreme acidic 20 and alkaline 21 , extreme low 22 and high temperature 19,23 , high temperature and pressure 24,25 , and deep subsurface 26 habitats. A combination of some of these extreme conditions also exists in some environments.…”
Section: Introductionmentioning
confidence: 99%
“…Jadi larutan hydrothermal terbentuk pada bagian akhir dari siklus pembekuan magma(67; 68).Larutan hydrothermal terjadi dalam beberapa cara(121)(122). Salah satunya peleburan magma yang terjadi oleh parsial basah yang mendingin dan mengkristal, air yang menyebabkan peleburan parsial basah dilepaskan(69)(70)(71)(72)(73)(74)(75)(76)(77). Namun tidak sebagai air murni (123), tetapi mengandung semua unsur yang dapat larut yang terdapat pada magma seperti NaCl dan unsur kimia: emas, perak, tembaga, timbal, zinc, merkuri dan molybdenum, yang tidak terikat kuarsa, feldspar, dan mineral lain dengan substitusi ion(78; 79).…”
unclassified